Direct speech, self-presentation and communities of practice : modern Greek narratives. - Lampropoulou, Sofia (Continuum literary studies., 2012)
This book deals with speech representation inGreek adolescents storytelling and investigates how members of differentcommunities of practice present themselves and other characters asinteractional protagonists through the stories they tell. The work puts forth adynamic approach that examines (direct) speech representation at the local andthe broader socio-cultural context in which it is embedded. The concept ofcommunity of practice accounts for direct speech variation, and direct speechis seen as the linguistic manifestation of shared repertoire of particularcommunities of practice. The book c.